Pengaruh Investasi dan Ekspor Terhadap Pertumbuhan Ekonomi Indonesia (Periode Tahun 2012 Sampai Dengan Tahun 2016) - Dedi Suhendro; Zulia Almaida Siregar (TANSIQ: Jurnal Manajemen Dan Bisnis Islam, 2019)
This study discusses the effects of investment and exports on Indonesia's economic growth (the period 2012 to 2016). The aim is to see how much influence investment and exports have on Indonesia's economic growth (the period 2012 to 2016). The amount of data determined is 20 (twenty) quarters from the data on the development of Gross Domestic Product (GDP), investment, and exports. The method to be used in this study is the research approach, data collection obtained from the official website of the Republic of Indonesia Investment Coordinating Board (ICB), Ministry of Trade (MOT), and Central Statistics Agency (CSA), literature related to the topic of research, data analysis, classic assumption tests, statistical tests, and focus group discussions (FGD). Partially the investment variable has an influence on the Gross Domestic Product (GDP) variable based on the ttest where tcount > ttable (7,783 > 2,10) while the significant level is 0 < 0,05. This means that the Ha hypothesis is accepted, meaning that partially the investment variable affects the Gross Domestic Product (GDP). Whereas for the export variable based on ttest where tcount < ttable (0,517 < 2,10) with a significant level of 0,612 > 0,05. This means that Ho is accepted, meaning that partially the export variable does not affect Gross Domestic Product (GDP).